Rational construction of LaFeO3 perovskite nanoparticle-modified TiO2 nanotube arrays for visible-light driven photocatalytic activity - Yu, Jiangdong (2019)
LaFeO3 nanoparticle-modified TiO2 nanotube arrays were fabricated through facile hydrothermal growth. The absorption edge of LaFeO3 nanoparticle-modified TiO2 nanotube arrays displaying a red shift to ~540 nm was indicated by the results of diffuse reflectance spectroscopy (DRS) when compared to TiO2 nanotube arrays, which means that the sample of LaFeO3 nanoparticle-modified TiO2 nanotube arrays had enhanced visible light response. Photoluminescence (PL) spectra showed that the LaFeO3 nanoparticle-modified TiO2 nanotube arrays efficiently separated the photoinduced electron–hole pairs and effectively prolonged the endurance of photogenerated carriers. The results of methylene blue (MB) degeneration under simulated visible light illumination showed that the photocatalytic activity of LaFeO3 nanoparticle-modified TiO2 nanotube arrays is obviously increased. LaFeO3 nanoparticle-modified TiO2 nanotube arrays with 12 h hydrothermal reaction time showed the highest degradation rate with a 2-fold enhancement compared with that of pristine TiO2 nanotube arrays.